Can P* Be a Basis for Core Inflation in the Philippines - Josef T. Yap (Philippine Institute for Development Studies (PIDS), 1996)
While previous studies utilizing P* indicates that the model is better applicable with large countries, the paper argues that the Philippine case should include a foreign gap price. Further work should also focus on estimating more appropriate values of Q* and V*.
Keywords: 330; econometric modeling